Business commonality, standardization and product cycles - Tsoulouhas, Theofanis (The journal of international trade & economic development, 2022)
By analyzing production with a continuum of tasks subject to common stochastic effects, the analysis shows that tension between business commonality and standardization is an important source of product cycles. The paper addresses the question of whether business commonality and standardization work in tandem or against each other in a general framework, when fragmentation of production is or is not possible due to contractual incompleteness or technology features. Unlike current literature, the analysis shows that a product cycle can be obtained even with complete contracts. This is so because retaining manufacturing within the firm enhances and exploits commonality in the early stages of production and, hence, reduces the moral hazard cost of providing incentives, which would be a hidden cost of outsourcing instead. Standardization later on can favor offshoring.